Remarkable abdominal androconial organs in Theages Walker, 1855 (Lepidoptera: Arctiidae) - Grados, Juan (2004)
Androconial organs on terga IV, V, VI and VII in species of the genus Theages Walker, 1855 are described, including its morphology and interspecific variation.